2017
DOI: 10.1002/hep4.1075
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the circadian metabolome in thioacetamide‐induced liver cirrhosis in mice

Abstract: Liver cirrhosis can disturb circadian rhythms, decreasing patient quality of life. Changes in metabolic products in cirrhosis are poorly understood. We evaluated changes in liver metabolism products using a thioacetamide‐induced mouse model of liver cirrhosis exhibiting circadian rhythm disturbance. Principal component analysis indicated that the circular progression found in the control group was disrupted in the thioacetamide group, and Jonckheere‐Terpstra‐Kendall analysis showed an imbalanced pattern of osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Thus, diurnal regulation of the GDH reactivity to its ligands addresses daily variations in energy metabolism which changes, among others, the levels of the GDH nucleotide regulators (Fustin et al, ; Reinke & Asher, ). Remarkably, the levels of 2‐oxoglutarate are not altered between the corresponding time points (Fujisawa, Takami, Matsumoto, Yamamoto, & Sakaida, ). Stabilization of GDH function (Figure a and b) through the adjustments of the GDH affinities to the oscillating nucleotide regulators (Table ) may contribute to this constant level of 2‐oxoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diurnal regulation of the GDH reactivity to its ligands addresses daily variations in energy metabolism which changes, among others, the levels of the GDH nucleotide regulators (Fustin et al, ; Reinke & Asher, ). Remarkably, the levels of 2‐oxoglutarate are not altered between the corresponding time points (Fujisawa, Takami, Matsumoto, Yamamoto, & Sakaida, ). Stabilization of GDH function (Figure a and b) through the adjustments of the GDH affinities to the oscillating nucleotide regulators (Table ) may contribute to this constant level of 2‐oxoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…Liver metabolic pathways and liver nuclear receptors are regulated by circadian clocks, reflected by oscillatory hormone binding, energy flux and expenditure and connected with metabolite production 77 . Studies have shown that disruption of the clock system plays a significant role in the development of alcoholic liver disease (ALD), liver fibrosis, liver cirrhosis, nonalcoholic fatty liver disease and hepatic carcinoma 78–81 …”
Section: The Role Of Chronobiology In Metabolic Pathwaysmentioning
confidence: 99%
“…77 Studies have shown that disruption of the clock system plays a significant role in the development of alcoholic liver disease (ALD), liver fibrosis, liver cirrhosis, nonalcoholic fatty liver disease and hepatic carcinoma. [78][79][80][81] Disruption of intestinal barrier function contributes to the devel- intestinal hyperpermeability. 82 The clock gene mPer2 controls circadian periods and its deficiency is associated with acute liver injury in mice by predisposing them to liver fibrosis by increasing HSC activation and inhibiting HSC apoptosis.…”
Section: The Role Of Chronobiology In Metabolic Pathwaysmentioning
confidence: 99%
“…These strong oxidizing products promote inflammation, fibrosis, and even carcinogenesis. Lipid metabolism shows an alteration from β-oxidation to ω-oxidation during liver cirrhosis[ 104 ]. Intriguingly, a metabolic switch from oxidative phosphorylation to glycolysis in hepatocytes in early-stage cirrhosis may satisfy the extreme energy requirements under such conditions[ 105 ].…”
Section: Altered Metabolism Of Liver Cancer and Its Influence On The mentioning
confidence: 99%